Investigation of protective surface film behavior of fluorine containing cover gas parameters on molten magnesium alloy - Vanli, Ali Serdar; Akdogan, Anil; Eryildiz, Meltem (PAMUKKALE UNIV, 2020)
Protection of molten magnesium is one of the most important issues for existing and potential magnesium users. An effective melt protection system is necessary for safety reasons as well as minimizing expensive metal losses. Since SF6 has an extremely high global warming potential, HFC-134a is an effective solution in many applications. In this study, surface films formed on molten AZ91A alloy under HFC-134a/N-2 atmosphere are examined in various parameters such as molten metal temperatures, exposure times, concentrations and flow rates of the protective gases. The obtained surface films as a result of the experiments were analyzed by optical microscope. The Taguchi experimental design method was used to determine the optimum process parameters. Process parameters provide the best protective layer on the melt; exposure time of 60 min, molten magnesium temperature of 660 degrees C, concentration of 0.30% vol., and the flow rate of protective gas mixture of 600 l/h. were determined.
Keywords: Fluorine-containing cover gas; HFC-134a; Surface film formation; Molten magnesium protection; Taguchi robust design; Engineering